Antioxidant and Antigenotoxic Actions of Gum Arabic on the Intestinal Mucosa, Liver and Bone Marrow of Swiss Mice Submitted to Colorectal Carcinogenesis. (24th March 2022) - Avelino, André Luís Nunes; Silva, Nina Victória Ribeiro e; Oliveira, Gilson Brito De; Silva, Antônio Adailson De Sousa; Cavalcanti, Bruno Coêlho; Jamacaru, Francisco Vagnaldo Fechine; Dornelas, Conceição Aparecida
Abstract: Colorectal carcinogenesis is characterized by oxidative stress and the formation of aberrant crypts in its initial stages. Gum arabic (GA) is a natural product with antioxidant properties, and, therefore, supposed antitumor action. The aim of this study was to evaluate the effects of GA on the formation of aberrant crypts, as well as the local, hepatic, and systemic genotoxicity and oxidative stress. We induced colorectal carcinogenesis in Swiss male mice, afterwards treated them with water, 2.5% GA or 5% GA via gavage for twelve weeks and then performed surgery in order to obtain samples to analysis (proximal and distal colon, liver, blood, and bone marrow). The number of aberrant crypts in the GA-treated animals was lower than in the control groups. Likewise, there was a decline of colonic, hepatic, and systemic genotoxicity and oxidative stress. These results reflect the antioxidant role of GA and may lead to the development of treatments that inhibit colorectal carcinogenesis.